PENGARUH PROMOSI WISATA, KUALITAS PELAYANAN DAN FASILITAS WISATA TERHADAP MINAT KUNJUNG ULANG MELALUI KEPUASAN PENGUNJUNG SEBAGAIVARIABEL INTERVENING PADA WISATAWANKAMPUNG BLEKOK KABUPATEN SITUBONDO - P, Sherly Ayu Fitriya; W, Dwi Perwitasari; A, Muhammad Iqbal; Windra C, Ayu Dita (Fakultas Ekonomi dan Bisnis, 2023)
The purpose of this study was to analyze and test the influence of tourism promotion, service quality and tourist facilities on repeat visit intentions through visitor satisfaction as an intervening variable in tourists from Blekok Village, Situbondo Regency. The population in this study is visitors or tourists from Kampung Blekok. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that tourism promotion has a significant effect on visitor satisfaction. Service quality has a significant effect on visitor satisfaction. Tourism facilities have a significant effect on visitor satisfaction. Tourism promotion has a significant effect on intention to revisit. Service quality has no significant effect on intention to revisit. Tourist facilities have no significant effect on intention to revisit. Visitor satisfaction has a significant effect on intention to revisit. Tourism promotion has a significant effect on intention to revisit through satisfaction. Service quality has a significant effect on intention to revisit through visitor satisfaction. Tourism facilities have a significant effect on intention to revisit through visitor satisfaction.